The Role of Management Information Systems in the E-Commerce Industry on the Shopee Application Program - Faeni, Dewi Puspaningtyas; Carolina, Anggraini Putri Otorus (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study examines how Management Information Systems (MIS) can enhance the efficacy and efficiency of e-commerce operations, with a specific emphasis on the Shopee app. SIM has become an essential tool for supporting business strategy, operational management, and customer interaction as a result of the information technology industry's rapid development. One of the top e-commerce sites in Southeast Asia, Shopee, has combined a number of SIM components, including supply chain management, market analysis, and customer data management, to optimize user experience and business performance. The study's findings indicate that managing the dynamics of the competitive e-commerce market and fostering Shopee's long-term growth and innovation depend heavily on the successful deployment of SIMs. The research's practical implications include suggestions for additional SIM development in e-commerce applications, with a focus on improving user experience and data security.